The Effect of The Company's Anti-Corruption Commitment on Earnings Management - RM Syah Arief Atmaja Wijaya; Vicky Vendy (Journal of Creative Power and Ambition (JCPA), 2026)
This study examines the relationship between a company's anti-corruption commitment and earnings management through disclosures referring to the GRI 205 Standard. Using a panel data regression analysis of 225 sustainability reports from companies listed on the IDX between 2019 and 2023, this research employs discretionary accruals for non-financial firms and Discretionary Loan Loss Provisions (DLLP) for financial firms as proxies for earnings management. The findings reveal that anti-corruption disclosure has a significant positive relationship with earnings management. However, significant difference was found in disclosure practices before and after the GRI 205 standard became effective. These results suggest that managers may use anti-corruption disclosures as a symbolic tool to create a positive reputation while potentially masking opportunistic behavior. This study contributes to the literature by exploring firm-level anti-corruption proxies and their impact on corporate transparency and information asymmetry in an emerging market context.